ALAT BATU DARI SITUS GUA GEDE, KECAMATAN NUSA PENIDA, KABUPATEN KLUNGKUNG, BALI (KAJIAN TIPOLOGI DAN FUNGSI) - Bayu Gusti Gineung Patridina, Esa Putra (Humanis; Volume 4. No. 3. September 2013, 2013)
1024x768 1024x768 T h is research i s aimed to get data about the types of stone tools based on the location and the sharpness angel. Furthermore , microscopic observation of the wear traces are fractures , striations , polish, and rounding . The shape and wear trace were analyzed with a rtefactual and c omparative technique to determind function of stone tool. Clasification of the 186 stone tools found in Gede Cave Site excavation in Box III , while analysis to trace wear of 27 stone tools that represent each type, subtype, and size. The analysis result shows that, the stone tools from B ox III of Gede Cave S ite can be classified into five types, namely: MLD , MTJ , MST , BLD , and BTJ . MLD type was used to s crape wood and leather , to whittle bone; to saw , and to perforate the leather. MTJ type was used to scrape wood , and leather; to plane wood; and to whittle bone. MST type was used to scrape the wood , leather, and plants. BLD and BTJ types were used to choppe wood. MLD.Cb , BTJ.Lr , MLD.Lr , and MTJ.Lr type cannot be predicted what its function . Normal 0 false false false EN-US X-NONE X-NONE Normal 0 false false false EN-US X-NONE X-NONE
Keywords: stone tools, type, function